Peer Support for Improving Student Engagement and Learning Outcomes in Postgraduate Public Health and Health Sciences: A Qualitative Study - Jinal Shashin Parmar; Sabuj Kanti Mistry; Sowbhagya Micheal; Tinashe Dune; David Lim; Stewart Alford; Amit Arora (Education Sciences)
Peer support is a widely recognized approach in higher education, improving learning efficiency, facilitating the exchange of knowledge, and helping students transition into university life through mutual help and collaboration. However, the evidence on the impact of peer support for an online study format, specifically in the context of postgraduate public health and health science students, is limited. This study evaluates a peer support program for postgraduate health students in the Social Determinants of Health subject at Western Sydney University who enrolled in Autumn 2021. Students were randomly allocated in groups of 4–5, and their experiences were evaluated using four focus groups discussions (FGDs). Inductive thematic analysis was conducted on the transcripts. The following three major themes were identified: (i) transitioning into university life and building academic support, (ii) promoting collaborative learning among peers, and (iii) engagement drivers, barriers, and suggested solutions. This study emphasizes the importance of peer support in aiding students’ transition into university, providing academic assistance, and addressing unexpected challenges such as the COVID-19 pandemic.